Eugene Jules Houdry papers - Houdry, Eugene Jules, 1892-1962.
Notes containing blueprints, mathematical calculations, formulas, and charts pertaining chiefly to catalysts and catalytic cracking in the petroleum industry; and remarks and papers concerning air pollution, petroleum chemistry, and public health. Also includes correspondence between Houdry's sons, Jacques H. Houdry and Pierre D. Houdry, and Jeffrey K. Stine.
French-American chemist, chemical engineer, and inventor.
Collection material in English and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Houdry, Jacques H. -- Correspondence; Houdry, Pierre D. -- Correspondence; Stine, Jeffrey K. -- Correspondence; Air -- Pollution; Catalysts; Catalytic cracking; Chemistry; Petroleum industry and trade; Public health; Chemical engineers; Chemists; Inventors